2005
DOI: 10.1021/bi051781p
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cooperativity and Site Selectivity in Human Ileal Bile Acid Binding Protein

Abstract: Human ileal bile acid binding protein (I-BABP) is a member of the family of intracellular lipid-binding proteins and is thought to play a role in the enterohepatic circulation of bile salts. Our group has previously shown that human I-BABP binds two molecules of glycocholate (GCA) with low intrinsic affinity but an extraordinary high degree of positive cooperativity. Besides the strong positive cooperativity, human I-BABP exhibits a high degree of site selectivity in its interactions with GCA and glycochenodeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(92 citation statements)
references
References 33 publications
7
81
0
3
Order By: Relevance
“…The binding features of BABPs appear difficult to capture, although recent studies have set important milestones in the atomic level description of BABP-ligand interactions (7)(8)(9)(10). It has been definitively ascertained that BABPs can form at least ternary complexes by hosting two ligand molecules inside a large protein cavity (11)(12)(13)(14).…”
Section: Intracellular Bile Acid-binding Proteins (Babp)mentioning
confidence: 99%
See 3 more Smart Citations
“…The binding features of BABPs appear difficult to capture, although recent studies have set important milestones in the atomic level description of BABP-ligand interactions (7)(8)(9)(10). It has been definitively ascertained that BABPs can form at least ternary complexes by hosting two ligand molecules inside a large protein cavity (11)(12)(13)(14).…”
Section: Intracellular Bile Acid-binding Proteins (Babp)mentioning
confidence: 99%
“…Cooperativity often arises from allosteric communication, a phenomenon that frequently escapes detection by common biochemical approaches (16). NMR and calorimetric studies performed on hI-BABP and on a series of mutants have attempted to identify the communication pathways between the two binding sites (9,10). Further interaction studies reported for other members of the BABP family describe the binding stoichiometry and affinity of the rabbit ileal protein (rI-BABP) (17) as well as the binding thermodynamics and crystallographic structure of fully complexed zebrafish ileal protein (zI-BABP) (13).…”
Section: Intracellular Bile Acid-binding Proteins (Babp)mentioning
confidence: 99%
See 2 more Smart Citations
“…[33] Tal como se había mencionado para el caso de los hepatocitos, es muy poco probable que los BAs atraviesen los enterocitos como monómeros libres, y el transporte intracelular es mediado por la proteína intestinal de unión a los ácidos biliares (IBABP), [34] una proteína pequeña que se encuentra citoplasmáticamente ligada al ASBT y que une los BAs (en proporción BA:IBABP 2:1) inmediatamente después de su entrada a la célula. [35] Finalmente el eflujo de BAs desde el enterocito a la sangre portal es mediado por la proteína transportadora heteromérica de solutos (OST).…”
Section: Transporte a Través De Los Enterocitosunclassified